2006
DOI: 10.1182/blood-2006-03-013151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genetic variations in platelet glycoproteins Ibα and VI on the risk for coronary heart disease events in postmenopausal women taking hormone therapy

Abstract: Millions of women still use postmenopausal hormone therapy (HT). We genotyped 2090 women in Heart and Estrogen/ progestin Replacement Study for functional polymorphisms in GP1BA and GP6 and assessed the coronary heart disease (CHD) event rate over 5.8 years of followup. In patients receiving placebo, there was an increased CHD death/myocardial infarction (MI)/unstable angina (UA) event rate in carriers of the GP1BA ؊5C allele (adjusted [adj] P ‫؍‬ .006). HT increased the hazard ratio (HR) of CHD events in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 49 publications
2
33
0
1
Order By: Relevance
“…This study was the first to show a diametrically opposite therapeutic response with hormone therapy in subjects with specific polymorphisms in platelet surface glycoproteins compared with subjects possessing the wild-type genotype, thus paving the way for future strategies in pharmacogenomic personalized medicine. 33 Platelet-specific polymorphisms in the GP IIIa, GP Ib␣, and GP VI genes have shown an association with an increased risk of cardiovascular events in some but not all studies (Table). The large meta-analysis by Ye et al 11 did not show significant overall associations between the GP Ia 807T, GP Ib␣ [-5]C, and GP IIIa 1565T gene variants and coronary disease, yielding a per-allele relative risk of 1.02 (confidence interval 0.97 to 1.08), 1.05 (confidence interval 0.96 to 1.13), and 1.03 (confidence interval 0.98 to 1.07), respectively.…”
Section: Plateletsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was the first to show a diametrically opposite therapeutic response with hormone therapy in subjects with specific polymorphisms in platelet surface glycoproteins compared with subjects possessing the wild-type genotype, thus paving the way for future strategies in pharmacogenomic personalized medicine. 33 Platelet-specific polymorphisms in the GP IIIa, GP Ib␣, and GP VI genes have shown an association with an increased risk of cardiovascular events in some but not all studies (Table). The large meta-analysis by Ye et al 11 did not show significant overall associations between the GP Ia 807T, GP Ib␣ [-5]C, and GP IIIa 1565T gene variants and coronary disease, yielding a per-allele relative risk of 1.02 (confidence interval 0.97 to 1.08), 1.05 (confidence interval 0.96 to 1.13), and 1.03 (confidence interval 0.98 to 1.07), respectively.…”
Section: Plateletsmentioning
confidence: 99%
“…The large meta-analysis by Ye et al 11 did not show significant overall associations between the GP Ia 807T, GP Ib␣ [-5]C, and GP IIIa 1565T gene variants and coronary disease, yielding a per-allele relative risk of 1.02 (confidence interval 0.97 to 1.08), 1.05 (confidence interval 0.96 to 1.13), and 1.03 (confidence interval 0.98 to 1.07), respectively. Abnormal platelet activation or aggregation has been linked to at least 3 genetic variants, including a polymorphism of the gene encoding the ␤-subunit of G proteins (GNB3), 33 a dimorphism within the P2Y 1 gene, 34 and 2 haplotypes within the P2Y 12 gene. 35 In small case-control studies, genetic variation of VAMP8, which is involved in platelet degranulation, has also shown an association with early-onset MI (Pϭ0.025), 36 whereas the minor sequence haplotype of the GP6 gene has been associated with an increased risk of MI among elderly individuals (Pϭ0.009).…”
Section: Plateletsmentioning
confidence: 99%
“…The percentage of subjects with at least 80% adherence to HT at year 6 declined to 45% in the hormone group and increased to 8% in the placebo group; again there were no significant differences between groups in the primary outcome (RH: 1.00; 95% CI: 0.77-1.29; p = 0.97) [4]. It is with this cohort that Bray and colleagues [1] evaluated platelet polymorphisms and the potential associations with CHD events as well as possible interactions with HT.For reprint orders, please contact: reprints@futuremedicine.com …”
mentioning
confidence: 65%
“…Platelets are involved in CHD events and platelet glycoprotein single-nucleotide polymorphisms may help to identify risk and treatment efficacy. It may become a plausible strategy in the future for clinicians to identify, by genotyping, high-risk patients who would benefit from HT to reduce CHD risk as well as to identify patients with neutral risk for whom HT could be harmful.In the March 2007 issue of Blood, Bray et al reported their findings on the effects of singlenucleotide polymorphisms (SNPs) in selected platelet glycoprotein (GP) genes on the risk for coronary heart disease (CHD) events in postmenopausal women with established CHD taking estrogen/progestin hormone therapy (HT) [1]. This is a salient issue as it is well known that the risk of CHD events increase in women after menopause and it was thought that HT would decrease this risk.…”
mentioning
confidence: 99%
See 1 more Smart Citation